Boundary Layer Flows Modelling, Computation, and Applications of Laminar, Turbulent Incompressible and Compressible Flows - Ramachandra Prasad, Vallampati; Silva, Valter; Cardoso, João (IntechOpen, 2023)
This book provides a comprehensive overview of boundary layer flows, including laminar and turbulent flows. Chapters discuss such topics as the nature of transition, the effect of two-dimensional and isolated roughness on laminar flow, and progress in the design of low-drag airfoils. They also present theoretical and experimental results in boundary layer flows and discuss directions for future research.